Pengaruh Harga, Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pengguna Transportasi Online Maxim Pada Mahasiswa di Yogyakarta The Influence Of Price, Promotion and Service Quality On Customer Satisfaction On Using Maxim’s Online Transportatio - Ani, Febri; Ratnaningtyas, Endah Marendah; Fathona, Citra Amira Putri; Nurani, Putri Ana (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
This research aims to analyze the influence of price, promotion and service quality on customer satisfaction of Maxim online transportation users among students in Yogyakarta.This research uses quantitative methods. Data collection was carried out by distributing questionnaires to students in Yogyakarta. The number of samples used was 100 people. Data collection techniques use questionnaires. Test multiple linear regression analysis, test the hypothesis using the t test and F test.The results of this research show that price and service quality partially have a significant effect on Maxim customer satisfaction among students in Yogyakarta, while promotion has no significant effect on Maxim customer satisfaction in Yogyakarta. Simultaneously, it was found that there was a significant influence between price, promotion and service quality on Maxim customer satisfaction among students in Yogyakarta.